Estimation above Ground Biomass of Private Forest Using Sentinel-1 and Sentinel-2 Satellite data (A Case Study in Gunung Kidul, Yogyakarta, Indonesia) - Askar (Prince of Songkla University, 2023)
Thesis (M.Sc., Environmental Management)--Prince of Songkla University, 2018